Legal consequences of execution of fiduciary collateral sold or pledged by the debtor - Jayadi Prasetya; Mochammad Nurwenda Faizal; Ana Harlina; Devi Mardianti (International Journal of Latin Notary, 2022)
The writing of this scientific work entitled "Legal Consequences of the Execution of Fiduciary Guarantees Sold or Pawned by Debtors" describes the execution of fiduciary guarantees that are not registered and the legal consequences by Law Number 42 of 1999 concerning Fiduciary Guarantees. This writing is motivated by the facts regarding illegal fiduciary agreements and the existence of fiduciary guarantee agreements made privately without registering fiduciary guarantee objects. Based on these facts, it is essential to raise 2 (two) issues regarding the procedures for executing fiduciary guarantees by laws and regulations and settlement of cases in the event of a sale or mortgage on goods subject to fiduciary guarantees while the goods are experiencing bad credit. The purpose of writing this journal is to find out the correct procedure for executing fiduciary guarantees and the legal consequences if the execution of fiduciary guarantees is carried out unilaterally and to find out the resolution of problems that arise regarding bad loans on objects used as fiduciary guarantees. The method used in this research is the descriptive analytical method with a normative juridical approach. The data used in this study is secondary data obtained from literature sources that are relevant to the issues discussed. The results of the study show that the execution of fiduciary guarantees for bad loans can be carried out directly by the leasing company if previously the leasing company has registered a fiduciary guarantee at the Fiduciary Guarantee Registration Office if it is not registered then to be able to execute fiduciary guarantees it must go through filing a civil lawsuit to court. Suppose the debtor sells or pawns the fiduciary collateral object, and lousy credit occurs while the fiduciary guarantee has been registered. In that case, the leasing company has the right over the object to seize and sell the object directly used as collateral.